1999
DOI: 10.1002/(sici)1096-9845(199911)28:11<1405::aid-eqe875>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental considerations for the design of non-linear viscous dampers

Abstract: SUMMARYTwo interrelated issues related to the design of non-linear viscous dampers are considered in this paper: structural velocities and equivalent viscous damping. As the e!ectiveness of non-linear viscous dampers is highly dependent on operating velocities, it is important to have reliable estimates of the true velocity in the device. This should be based on the actual relative structural velocity and not the commonly misused spectral pseudo-velocity. This is because if spectral pseudo-velocities (PSV) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 2 publications
2
58
0
1
Order By: Relevance
“…To further address these issues, this study has adopted modified damping approximations proposed by Lin and Chang [21] coupled with the reduction in equivalent viscous damping due to the pinched nature of the real hysteresis curves, as introduced by Pekcan et al [22]. Based on recent studies by Lin and Chang [21], confirmed by Lin et al [23], and modified herein as part of the present study, the damping-related reduction factors, B a , B v , and B d can be calculated as a function of effective damping,  eff as follows: The damping factor for the constant spectral velocity range, B v can be calculated by linear interpolation between B a and B d based on period or spectral displacement.…”
Section: Rapid Ida-eal Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…To further address these issues, this study has adopted modified damping approximations proposed by Lin and Chang [21] coupled with the reduction in equivalent viscous damping due to the pinched nature of the real hysteresis curves, as introduced by Pekcan et al [22]. Based on recent studies by Lin and Chang [21], confirmed by Lin et al [23], and modified herein as part of the present study, the damping-related reduction factors, B a , B v , and B d can be calculated as a function of effective damping,  eff as follows: The damping factor for the constant spectral velocity range, B v can be calculated by linear interpolation between B a and B d based on period or spectral displacement.…”
Section: Rapid Ida-eal Methodologymentioning
confidence: 99%
“…Based on recent studies by Lin and Chang [21], confirmed by Lin et al [23], and modified herein as part of the present study, the damping-related reduction factors, B a , B v , and B d can be calculated as a function of effective damping,  eff as follows: The damping factor for the constant spectral velocity range, B v can be calculated by linear interpolation between B a and B d based on period or spectral displacement. Total effective viscous damping,  eff , can be estimated by using the method proposed by Pekcan et al [22]:…”
Section: Rapid Ida-eal Methodologymentioning
confidence: 99%
“…Pekcan et al [7] investigated the seismic performance of a class of dampers conforming to Equation (1). Across a broad spectrum of response, they showed that such …”
Section: Theoretical Device Characterisation For Design Applicationsmentioning
confidence: 99%
“…where 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w (7)- (9); T = the period of the structure; and T d = the period at the junction of the constant spectral velocity and displacement portions of the spectra. Using Equation (10) accelerationperiod seismic demand spectra for normal soil (where PGA = F v S 1 and F a S s = 2.5F v S 1 ) are presented in Figure 10.…”
Section: Design Implementationmentioning
confidence: 99%
“…The nonlinear viscous force is characterized by the damper exponent α typically ranging from 0.2 to 1 [29] and η the damping coefficient (related to the generalized mass of the system). The excitation is modelled by a white noise W (t) modulated by a time window a(t) defined as…”
Section: Probability Of Exceedance Of a Nonlinear Sdof Oscillatormentioning
confidence: 99%